ADVANCED CALCULUS FOR SCIENCE AND ENGINEERING STUDENTS - Abd Wahid Md. Raji; Ismail Kamis; Mohd Nor Mohamad; Ong, Chee Tiong (Penerbit UTM Press, 2021)
This book was written by a group of experienced mathematics lecturers from the Department of Science and Mathematics at Universiti Tun Hussein Onn and the Department of Mathematical Sciences at Universiti Teknologi Malaysia. This textbook is intended primarily for second and third-year students who study advanced calculus in science and engineering fields in Institutions of Higher Learning in Malaysia. The content of each chapter is organized cognitively so as to guide the student to acquire the essential concepts and develop the mathematical thinking skills systematically. Among the helpful features in the book are: More than 340 solved examples, with complete steps of solution to help student understanding the basic processes. Quizzes, which are short questions at the end of each sections to consolidate the skills acquired. Exercise, at the end of each chapter, to help student recapitulate and reinforce learning. More than 600 questions are arranged according to increasing degrees of difficulties. Many of these questions are posed to challenge student's thinking processes and to help them develop mathematical thinking skills. Tables showing formulae for differentiation, integration and trigonometric identities are included at the end of this book.